Black Economic Empowerment and Quota Allocations in South Africa's Industrial Fisheries. Issue 5 (8th August 2022) - Vilakazi, Thando; Ponte, Stefano
ABSTRACT: Power asymmetries in the governance of value chains mean that inequalities in access to resources and share of value added are skewed against smaller players. Policies enforcing market rules and ensuring fairness are ineffective when power is deeply entrenched, necessitating different rules to address such inequalities. South Africa's Black Economic Empowerment (BEE) policies and competition laws target economic redress and inclusion of historically disadvantaged people in business ownership and control of economic activities. BEE criteria have been embedded in many industry charters and implementation codes, and competition law is well established and effectively implemented. Yet, the impacts of these instruments have been limited and slow, especially in sectors where a few companies dominate. This article examines the interactions between value chain dynamics and industrial fishery quota allocations, BEE policy and competition dynamics in the hake deep‐sea trawl fishery sector. It shows that, even in one of the most regulated sectors of South Africa's economy, large incumbents retain a disproportionate amount of power vis‐à‐vis smaller players. The article concludes that if rules protect incumbency, inequality will be sustained. Quota allocations, transformation and competition regulation should go hand in hand to facilitate the effective participation of black‐owned businesses as competitors in value chains.